DETEKTOR EKSPRESI WAJAH MANUSIA - Rionaldi Ali (IIB Darmajaya, 2016)
Human face expression is on of the sign of human behavior. Face expression can deliverhuman being tought, so that we can recognize their emotion. But when emotion reach certain of level, details of human expression is lost.Our research will describeand explainabout a technique that could detect human face expression to to determining emotion when persons is in happy emotion, anger, sad, or afraid. Keywords : Face Expression, Emotion Detector